Penggunaan Window Light Sebagai Sumber Pencahayaan Alami dalam Fotografi - Desipriani Desipriani (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The use of window light as a natural lighting source in photography offers a unique blend of softness and directionality that enhances the subject's features while creating an aesthetically pleasing atmosphere. This study explores the characteristics of window light, including its intensity, color temperature, and the effects of various window placements on the final image. By understanding how to manipulate window light, photographers can achieve professional-quality results without the need for expensive lighting equipment. The findings emphasize the importance of natural light in creating dynamic and expressive photographs, making it a valuable resource for photographers at all skill levels.